The Role of Green Innovation in Strengthening CSR to Enhance Sustainable Performance in the Era of the Global Climate Crisis - Sidharta, Eka Ananta; Asyik, Nur Fadjrih; Rusdiyanto; Susilo, Heryanto; Mustakim (Complex Systems Informatics and Modeling Quarterly, 2025)
This study examines the mediating function of Green Innovation in the association between corporate social responsibility (CSR) initiatives and sustainable performance. It adopts a quantitative approach by collecting data from 129 recycling companies across various provinces in Indonesia through structured questionnaires distributed online. Partial Least Squares Structural Equation Modeling was conducted using the SmartPLS software to examine Green innovation’s function as a mediator between sustainable performance and CSR. The results indicate that green innovation has a pivotal mediating role between CSR initiatives and sustainable performance in Indonesia’s recycling sector. These results underscore the importance of long-term commitment and strategic alignment in overcoming short-term costs and complexities associated with implementing sustainability initiatives in an emerging industry. This study reveals the strategic role of companies in natural resource management as key to achieving sustainable performance amid the global climate crisis. It highlights the integration of environmental efforts, competitive capabilities, and sustainable innovation as a holistic approach rarely explored in the recycling industry of developing countries such as Indonesia. Positioning company capability as the main mediator, the study offers new insights into creating sustainable added value and strategic guidance for policymakers and practitioners. Additionally, it supports environmental, social, and governance and circular economy agendas, contributing significantly to the transition toward a green economy and sustainable development. In the domain of economics, this research can be attributed to the JEL Classification Code Q01; Q56; M14; L26; O31.